Interaction between the diatom Cylindrotheca closterium and a siliceous mortar in a silica-limited environment. (28th February 2022) - Georges, Marine; Bourguiba, Amel; Boutouil, Mohamed; Chateigner, Daniel; Jolly, Orianne; Claquin, Pascal
Highlights: Evaluate the ability of a benthic diatom species, Cylindrotheca closterium, to use the mortar from artificial marine structure as a silicon (Si) source for their own metabolism and growth. Monitoring the Dissolution kinetics of the silica from mortar. Monitoring the Batch cultures performance of C. closterium under silicon limitation with or without the presence of mortar. Acclimatation of C. closterium to maintain growth under limited Si condition by modifying some of their morpho-functional traits, photosynthetic parameters, silicification index. Abstract: Man-made infrastructures are wildly developed in many coastal ecosystems. Understanding and improving the positive interactions between concrete maritime infrastructures and biological components remains one of the ecological engineering challenges. The aim of this study is to evaluate the ability of a benthic diatom species, Cylindrotheca closterium ( C. closterium ), to use the mortar of artificial marine structure as a silicon source for their own metabolism and growth. Diatoms are the dominant class of primary producer in many ecosystems. Diatoms need to absorb dissolved silica (dSi) in the form of Si(OH)4 in order to synthesize their cell wall (the frustule). Batch cultures of C. closterium were performed under silicon limitation with or without the presence of mortar. First, the dissolution kinetics of silica from mortar in seawater were studied. Thereafter, the interaction between microalgae and dissolution kinetic properties were explored along with diatom biological parameters (Growth, biogenic silica per cell, biovolume, silicification degree and photosynthetic parameters). The dSi released by the mortar increases from the first days in the medium. Subsequently the Si(OH)4 concentration decreased when microalgae were introduced into the medium associated to a parallel increase of the biogenic silica showing that cells are able to use dSi from the mortar to elaborate their frustule. The study also identified modifications of some of morpho-functional traits of C. closterium to maintain growth under limited Si conditions. This study shows how the benthic diatom C. closterium are able to benefit and acclimate from silica input provided by immersed artificial structures.